Sentry Bioconvertible Inferior Vena Cava Filter: Study of Stages of Incorporation in an Experimental Ovine Model - Peter A. Gaines; Frank D. Kolodgie; Gordon Crowley; Steven Horan; Megan MacDonagh; Emily McLucas; David Rosenthal; Ashley Strong; Michael Sweet; Deepal K. Panchal (International Journal of Vascular Medicine)
The Sentry inferior vena cava (IVC) filter is designed to provide temporary protection from pulmonary embolism (PE) and then bioconvert to become incorporated in the vessel wall, leaving a patent IVC lumen. Objective. To evaluate the performance and stages of incorporation of the Sentry IVC filter in an ovine model. Methods. Twenty-four bioconvertible devices and 1 control retrievable filter were implanted in the infrarenal IVC of 25 sheep, with extensive daily monitoring and intensive imaging. Vessels and devices were analyzed at early (≤98 days, n = 10) and late (180 ± 30 days, n = 14 study devices, 1 control) termination and necropsy time-points. Results. Deployment success was 100% with all devices confirmed in filtering configuration, there were no filter-related complications, and bioconversion was 100% at termination with vessels widely patent. By 98 days for all early-incorporation analysis animals, the stabilizing cylindrical part of the Sentry frame was incorporated in the vessel wall, and the filter arms were retracted. By 180 days for all late-incorporation analysis animals, the filter arms as well as frames were stably incorporated. Conclusions. Through 180 days, there were no filter-related complications, and the study devices were all bioconverted and stably incorporated, leaving all IVCs patent.